Sumbangan Athanasius dari Aleksandria dalam Pembentukan Ajaran Trinitas - Sendjaja, Hendri Mulyana (Faculty of Theology Duta Wacana Christian University, 2018)
Abstract The intellectual struggles and adventures of Christian thinkers in Alexandria in the first centuries produced an overarching effect to the doctrines of Christian faith, which survived to the present day. One of those doctrines is the doctrine of the Trinity. The study of the thought of Athanasius of Alexandria in regards of God, Jesus Christ, and the Holy Spirit, through his works such as Contra Gentes-De Incarnatione, Contra Arianos I-III, and Epistola ad Serapionem, speaks for itself the contribution he made to solidify the doctrine of the Trinity. For him, the doctrine expresses the eternal communion among the Father, the Son and the Holy Spirit, which in effect brings benefi t to us. The construction of the doctrine is inseparable from the Church tradition which owed to the ecclesiastical biblical exegesis, and the construction of the theological methods, and the soteriological perspective. Abstrak Pergumulan dan petualangan intelektual pemikir-pemikir Kristen di Aleksandria pada abad-abad pertama menghasilkan ajaran-ajaran iman Kristen yang bertahan sampai sekarang. Salah satu ajaran-ajaran itu adalah ajaran Trinitas. Penelitian pemikiran Athanasius dari Aleksandria tentang Allah, Yesus Kristus, dan Roh Kudus, dalam karyanya Contra Gentes-De Incarnatione, Contra Arianos I-III, dan Epistola ad Serapionem, membuktikan bahwa Athanasius memberikan sumbangan yang signifi kan dalam pembentukan ajaran Trinitas yang lebih mantap. Bagi Athanasius, ajaran Trinitas mengungkapkan persekutuan yang erat antara Bapa dan Anak dan Roh Kudus secara kekal untuk kepentingan kita. Ajaran ini tidak lepas dari tradisi iman Gereja yang bertolak dari penggunaan metode penafsiran Alkitab dan metode berteologi dalam lingkup ekklesiastikal, serta perspektif soteriologis.